Analisis Kesulitan Belajar Matematika Materi Bangun Datar SDN Karang Tengah 7 - Ramadhan, Yusuf Fadillah; Jannah, Raudhatul; Ariq, Muhammad; Magdalena, Ina (Lembaga Yasin AlSys, 2023)
This study aims to (1) reveal the types of difficulties experienced by fourth grade students at Karang Tengah 7 Public Elementary School, and (2) describe the mathematics learning difficulties experienced by fourth grade students at Karang Tengah 7 Elementary School. This study used an analytic descriptive method with a qualitative. The subjects in this study were students of class IV A at SD Negeri Karang Tengah 7. The subjects in this study were determined using purposive sampling. Data collection techniques used in this study were used by means of essay tests and interviews. The data analysis technique used in this study is data reduction, data presentation, and finally drawing conclusions. The results of the study (1) learning difficulties in mathematics experienced by fourth grade students at SD Negeri Karang Tengah 7, namely spatial relationship disorders, visual perception abnormalities, visual motor associations, difficulty using symbols, difficulties in language and reading, and (2) students who experience relationship disorders 12 students in the room, 14 students with visual perception abnormalities, 13 students with visual perception abnormalities, 8 students with difficulty understanding symbols, 2 students with language and reading difficulties.